Dialog creates new technology platform (Computers in Libraries, 2004)
Dialog announced that it has developed and launched a new comprehensive technology platform for its line of business information, news, and market research services. The new platform features the launch of Dialog's new SmartTerms taxonomy, which uses more than 855,000 terms, including 3,200 industry terms, 375 subject terms, 500 geographic location terms, 800,000 company names, 8,000 publication names, and 46,000 related and secondary terms.